2002
DOI: 10.1080/00365510260296492
|View full text |Cite
|
Sign up to set email alerts
|

Determination of vascular endothelial growth factor (VEGF) in circulating blood: significance of VEGF in various leucocytes and platelets

Abstract: Circulating neutrophils contain considerable amounts of VEGF that contribute to high VEGF levels in lysed whole blood. VEGF in circulating platelets contributes to high VEGF levels in serum and lysed whole blood. Allowing whole blood samples to clot for between 2 and 6 h before serum is collected reduces time-dependent, non-uniform release of VEGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 17 publications
8
90
0
4
Order By: Relevance
“…It is in fact, known that neutrophils transport 70% of VEGF amounts in the blood, and that the precursors of this blood cell lineage express VEGF-2/FLT1 receptor on their membrane whose engagement is critical for their maturation. 32,33 In line with this hypothesis we report that bevacizumab administration is followed by progressive granulocyte depletion and functional inactivation as suggested by the finding that the treatment is associated to a decrease of serum myeloperoxidase levels.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tsupporting
confidence: 63%
“…It is in fact, known that neutrophils transport 70% of VEGF amounts in the blood, and that the precursors of this blood cell lineage express VEGF-2/FLT1 receptor on their membrane whose engagement is critical for their maturation. 32,33 In line with this hypothesis we report that bevacizumab administration is followed by progressive granulocyte depletion and functional inactivation as suggested by the finding that the treatment is associated to a decrease of serum myeloperoxidase levels.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tsupporting
confidence: 63%
“…This observation is not surprising considering that neutrophils transport more that 70% of VEGF in the blood and that peripheral blood cells express VEGF-2/FLt1 receptor on their membrane whose activation is important for their maturation. 28,29 An additional study is presently ongoing to explain the significant decline in lymphocytes which directly correlated with bevacizumab dosage and to evaluate which lymphocyte subset is affected by the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded reference Caine et al (2004) because the data reported was three orders of magnitude higher than those reported in other studies. Concentrations are calculated using volume of a platelet, 9 fl (Lentner et al, 1984), and quantity is determined by multiplying the concentration by the total volume of platelets in the blood (cancer: 14.18 ml, healthy: 11.15 ml) (Lentner et al, 1984;Werther et al, 2002b). Results are summarised in Figure 3A and B.…”
Section: Compartmental Analysis and Data Interpretationmentioning
confidence: 99%
“…A number of studies report correlation between platelet counts and serum VEGF (Werther et al, 2002b;Caine et al, 2004), and higher serum VEGF levels per platelet in cancer (Salven et al, 1999a;Kusumanto et al, 2003). The importance of platelet-derived VEGF in cancer may be due to VEGF released upon thrombin activation by platelets, with VEGF inducing vascular permeability and in doing so further promoting coagulation (Mohle et al, 1997;Verheul and Pinedo, 1998).…”
mentioning
confidence: 99%